Biochar applications for treating potentially toxic elements (PTEs) contaminated soils and water: a review - Zhang, Xu; Zou, Guoyan; Chu, Huaqiang; Shen, Zheng; Zhang, Yalei; Abbas, Mohamed H. H.; Albogami, Bader Z.; Zhou, Li; Abdelhafez, Ahmed A. (Frontiers in Bioengineering and Biotechnology, 2023)
Environmental pollution with potentially toxic elements (PTEs) has become one of the critical and pressing issues worldwide. Although these pollutants occur naturally in the environment; however, their concentrations are in continuous increase, probably as the consequences of anthropic activities. These pollutantsy are very toxic; even at very low concentrations; hence possess undesirable ecological impacts. Thus, the cleanup of polluted soils and water has become an obligation to ensure safe handling of the available natural resources. Several remediation technologies can be followed to attain successful remediation, i.e., chemical, physical, and biological procedures; yet many of these techniques are expensive and/or may negative impacts on the surroundings. Recycling agricultural wastes still represents the economic, promising safe and successful approach to achieve a healthy and sustainable environment. Briefly, biochar acts as efficient biosorbents for many PTEs in soils and waters. Furthermore, biochar can reduce considerably concentrations of herbicides from solutions. This review article explains the main reasons beyond increasing levels of potentially toxic element (PTEs) in the environment and their negative impacts on the ecosystem. Moreover, it describes briefly pros and cons of using conventional methods for soil and water remediation then clarifies the reasons beyond using biochar in the clean-up practice of polluted soils and waters, either solely or in combination with other methods such as phytoremediation and soil washing technologies to attain more efficient remediation protocol for removal of some PTEs, i.e., Cr and As from soils and water.The environment is defined as -the sum total of all the surroundings, including natural resources and other factors that may affect the growth and development of living organisms. It is the place (soils, water, air and food) that needs to be protected and